Anti-neuroinflammatory effects of cudraflavanone A isolated from the chloroform fraction of Cudrania tricuspidata root bark. (1st January 2018) - Kim, Kwan-Woo; Quang, Tran Hong; Ko, Wonmin; Kim, Dong-Cheol; Yoon, Chi-Su; Oh, Hyuncheol; Kim, Youn-Chul
Abstract: Context: Cudrania tricuspidata Bureau (Moraceae) is an important source of traditional Korean and Chinese medicines used to treat neuritis and inflammation. Objective: The anti-neuroinflammatory effects of cudraflavanone A isolated from a chloroform fraction of C. tricuspidata were investigated in LPS-induced BV2 cells. Materials and methods: Cudraflavanone A was isolated from the root of C. tricuspidata, and its structure was determined by MS and NMR data. Cytotoxicity of the compound was examined by MTT assay, indicating no cytotoxicity at 5–40 μM of cudraflavanone A. NO concentration was measured by the Griess reaction, and the levels of PGE2, cytokines and COX-2 enzyme activity were measured by each ELISA kit. The mRNA levels of cytokines were analysed by quantitative-PCR. The expression of iNOS, COX-2, HO-1, NF-κB, MAPKs and Nrf2 was detected by Western blot. Results: Cudraflavanone A had no major effect on cell viability at 40 μM indicating 91.5% viability. It reduced the production of NO (IC50  = 22.2 μM), PGE2 (IC50  = 20.6 μM), IL-1β (IC50  = 24.7 μM) and TNF-α (IC50  = 33.0 μM) in LPS-stimulated BV2 cells. It also suppressed iNOS protein, IL-1β and TNF-α mRNA expression. These effects were associated with the inactivation of NF-κB, JNK and p38 MAPK pathways. This compound mediated its anti-neuroinflammatory effects by inducing HO-1 protein expression via increased nuclear translocation of Nrf2. Discussion and conclusions: The present study suggests a potent effect of cudraflavanone A to prevent neuroinflammatory diseases. Further investigation is necessary to elucidate specific molecular mechanism of cudraflavanone A.